Cathelicidins—a rich seam of antimicrobial peptides waiting for exploitation - Tossi, Alessandro; Gerdol, Marco; Caporale, Andrea; Pacor, Sabrina; Mardirossian, Mario; Scocchi, Marco; Prickett, Michael D.; Manzini, Giorgio; Gennaro, Renato (Frontiers in Drug Discovery, 2024)
Cathelicidins are a ubiquitous family of host defence antimicrobial peptides in vertebrate animals.Unlike other antimicrobial peptide families, it is defined by a large and relatively well conserved proregion rather than by the mature bioactive peptides themselves, which are highly diverse and conform to at least five different structural types, resulting in distinct modes of action. Cathelicidinderived host defence peptides have a pleiotropic role in immunity, displaying both a direct antimicrobial activity and the ability to boost other host responses to infection and injury. The presence of a relatively well conserved proregion attached to a vast repertoire of structurally and functionally diverse peptides allows mining the increasing number of vertebrate genomes for lead sequences to potentially useful new anti-infective and/or immunomodulatory agents. This should increase the number of cathelicidin-based peptides entering clinical trials, which has been limited to date, despite considerable efforts in the last two decades.